Evaluasi Resistensi terhadap Metoksifenozida pada Spodoptera exigua di Jawa - I. Indriyati Wibisono; Y. Andi Trisyono; Edhi Martono; Aziz Purwantoro (Universitas Gadjah Mada, 2007)
The objective of this research was to know the resistance level of beet armyworm Spodoptera exigua to methoxyfenozide. The lara were collected from the shallot production areas in the districts of Nganjuk (East Java), Bantul and Kulonprogo (Yogyakarta Specia Territory) and Brebes (Central JAva). The bioassay used first instars of S. exigua with artificial diets that had been dipped in a series of methoxyfenozide solutions. Larval mortality was recorded at 72 hours after the exposure. The LC50 value of methoxyfenozide for the population from Sanden (Bantul) was the lowest (0.53 ppm) among 16 tested population, therefore it was used as refenrence population to determine the resistance ratio (RR) values of other populations. The RR values of the tested populations varied from 1 to 240,8 times. Population collected from Wanasari (Brebes) was found to have the highest level of resistance of methoxyfenozide as a result of using methoxyfenozide intensively to S. exigua controlling.